Analisis Penggambaran Desain Ilustrasi Makanan pada Webtoon Slice of Life “Mukbang Life” - Magdalena, Elisa; Susanti, Elizabeth (Universitas Komputer Indonesia, 2024)
Webtoon is a comic that has emerged and is in great demand among young people online in the form of a website that is released continuously following a schedule determined by the licensed comic writer. This research aims to discuss the design of food illustrations in the Webtoon